Ринок інформаційних технологій в Україні та світі - Карп’як, А. О. (Видавництво Львівської політехніки, 2018)
Досліджено стан ринку ІТ технологій в Україні, його структуру та стан розвитку його структурних елементів. Проведено аналіз підходів у формалізації структури ІТ ринку. Проведено аналізування якості і обсягу таких структурних елементів ринку, як товарна пропозиція, попит та ринкові ціни. Обґрунтовано причини низького попиту на внутрішньому національному та недостатнього попиту на світовому ринку на продукт українського ІТ ринку. Обґрунтовано процес визначення ефективності маркетингової діяльності, виявлено основні чинники, які впливають на її рівень.

The article investigates the state of the market of IT technologies in Ukraine, its structure and the state of development of its structural elements. A comparative analysis of the contribution of the services market to GDP of Ukraine and developed countries of the world was conducted. It is emphasized the prevailing influence of the sphere of services and its product in the modern economy. The dynamics of the share of services related to the processing and transmission of information is investigated. It is substantiated that given the scale of added value in the field of information and telecommunication technologies, this sphere of human activity has grown into a powerful industry. The reasons for the rapid and steady growth of the IT industry in Ukraine are described, namely: for the IT industry, the basic means are not the means of production, but the information which is much higher in the post-industrial society; than raw materials, products of agriculture or industry; a sufficiently high level of fundamental physical and mathematical and special technical education; optional physical location. The analysis of the implementation of the information technology market of the main functions of the market is carried out. The analysis of approaches in the formalization of IT market structure is carried out. It is stated that the most advanced sphere in the field of information technologies, intellectual and intermediary electronic services is the intellectual sphere and, in particular, outsourcing. The analysis of quality and volume of such structural elements of the market as commodity supply, demand and market prices has been carried out. It is shown that the product supply of the IT market consists of a number of components. In particular, the number and quality of specialists, serving as the main product offer of Ukraine on the world IT market. There is a shortage of specialists in this profile. It is noted that so far in terms of player scale, there is an unbalanced market for software development. The reasons of low demand for internal domestic and insufficient demand on the world market for the product of the Ukrainian IT market are substantiated. The process of determining the effectiveness of marketing activity is substantiated, the main factors influencing its level are revealed.
Market of information technology in Ukraine and the world
Keywords: ІТ ринок; структура ІТ ринку; структурні елементи ІТ ринку; товарна пропозиція; попит; ринкові ціни; IT market; structure of IT market; structural elements of IT market; product supply; demand; market prices; 33.02; 378; 338.2